Tracking Loach politics, practices, production - Archibald, David 1964- (Political cinemas, 2023)
Tracking Loach presents a ground-breaking and unique contribution to the study of cinema. Archibald was granted unprecedented access to observe one of world cinema's most celebrated and controversial filmmakers, Ken Loach, while he was making the 2012 feature 'The Angels Share', which received The Jury Prize at the Cannes Film Festival. This book draws on this knowledge to offer a first-hand account of the director's celebrated working methods, supplemented with insights gleaned from the British Film Institute's Loach archive, and analysis of his wider output and film-related political activity. Archibald has been 'Tracking Loach' for over three decades, as film viewer, film critic and film academic, and this inside perspective not only offers fresh insights into Loach's films and how they are made, but also highlights the benefits of production studies to the understanding of cinema more broadly